PROXIMATE AND MINERAL PROFILING OF INDIGENOUS GRAINS: A COMPARATIVE ANALYSIS OF TRITICUM AESTIVUM L., PENNISETUM GLAUCUM, AND SORGHUM BICOLOR L. FROM KOGI STATE MARKETS - Abdullahi, Bilkisu Idris; Eneogwe, Godfrey Okechukwu; Ibrahim, Esther Izihyi; Atumeyi, Anthony Ugbedeojo; Kani, Zeenatu Ibrahim; Chris, Magret Ahuoiza (FUDMA JOURNAL OF SCIENCES, 2025)
This study aimed to evaluate and compare the proximate composition and mineral content of grains from Triticum aestivum L, Pennisetum glaucum and Sorghum bicolor L, all collected from Kogi State, Nigeria, using standard analytical methods. Each analysis was conducted in triplicate, and differences among samples were evaluated using one-way ANOVA at a significance level of P ≤ 0.05. The results revealed significant nutritional differences across the grains. Notably, Pennisetum glaucum exhibited the highest levels of ash content (2.90±0.15%), crude fat (3.53±0.16%), fibre (8.80±0.33%) and the lowest moisture content (7.23±0.43%). In contrast, Triticum aestivum had the highest crude protein (12.43±0.55%) and carbohydrate content (70.74±0.55%). In terms of mineral content (mg/100g), the grains contained significant levels of essential minerals. Pennisetum glaucum had the highest concentrations of calcium (44.24±0.28 mg/100g), potassium (462.65±0.56 mg/100g), sodium (10.58±0.24 mg/100g) and zinc (2.88±0.24 mg/100g). Meanwhile, Triticum aestivum demonstrated the highest phosphorus concentration at 338.23±0.54 mg/100g, and Sorghum bicolor had the highest magnesium content at 162.48±0.21 mg/100g. Although all grains were nutritionally rich, their compositions varied significantly, highlighting their complementary roles in human diets. These findings support the dietary relevance of these indigenous grains in food fortification and nutritional interventions.
Keywords: Proximate composition, mineral composition, Triticum aestivum L, Pennisetum glaucum and Sorghum bicolor L; Proximate composition; Mineral composition; Triticum aestivum L; Pennisetum glaucum; Sorghum bicolor L